Heteroatom-embedded Mellitic Triimido COFs for efficient proton conduction - Keiichiro Maegawa; Mateusz Wlazło; Vellaichamy Joseph; Krzysztof Łyczko; Yaroslav Korol; Marek J. Potrzebowski; Atsunori Matsuda; Atsushi Nagai (Scientific Reports)
Abstract Ionic covalent organic frameworks (iCOFs) are promising materials for energy storage devices due to their ionic functional groups, which facilitate ion transport, and their highly ordered pores of their frameworks, which provide ideal pathways for long-term ion transport under harsh electrochemical conditions. In this study, we attempted for the first time to synthesize an unprecedented iCOF using a heteroatom-embedded mellitic triimido COF framework that enables practical ion channels on the Angstrom scale. This iCOF was subsequently evaluated as an anhydrous proton-conducting material. The heterocyclic pyridine group of the 2,5-diaminopyridine (DAPy) linker plays an important role, not only as an AB stacking-inducing group but also as a proton acceptor that interacts with impregnated H3PO4. The resulting PA@MTI-DAPy-COF exhibited high proton conductivity of 3.68 × 10–2 S cm–1 at 150oC under anhydrous conditions. This work paves the way for constructing efficient proton-conducting channels by leveraging the stacking structure of COF skeletons.